Extent of Women’s Participation in Decision Making in Peri-Urban Smallholder Integrated Farming Systems - ANITROSA INNAZENT; NAMITHA KRISHNA; JACOB D (Journal of Extension Education, 2023)
The present study was undertaken in peri-urban panchayats of Thiruvananthapuram city, the state capital of Kerala, India. The objective was to ﬁnd out the extent of women’s participation in decision making in peri-urban smallholder integrated farming systems and factor inﬂuencing their participation. The study utilized ex-post facto research design and data collection was done through interview schedule. The results revealed that the majority of farm women took decisions jointly with other male household members. The extent of women’s participation in decision making was medium. Independent variables such as economic motivation, market orientation, experience in integrated farming systems, social participation, material possession, annual income, and education level were crucial factors in women’s participation in decision making in peri-urban smallholder integrated farming systems.